Management of peri-prosthetic fractures around total hip arthroplasty: a contemporary review of surgical options - Davenport, Dominic; Hutt, Jonathan R.; Mitchell, Philip A.; Trompeter, Alex; Kendoff, Daniel; Sandiford, Nemandra A. (Annals of Joint, 2018)
The burden of periprosthetic fractures is increasing with increasing volumes of total hip arthroplasty. These injuries often occur in older patients with more significant co-morbidity and osteopenia. Management of these injuries is often resource intensive and can present significant socioeconomic challenges. Understanding the principles of surgical management these cases and recognising when fixation or replacement is required is critical. The aim of this article is to present a contemporary evidence-based review of the surgical fixation options for management of periprosthetic fractures in the presence of well-fixed or loose components.